Peran Lingkungan Sekolah dalam Pembentukan Karakter Disiplin di MTsN 4 Musi Banyuasin - Kasinyo Harto; Tutut Handayani; Mukti Mukti; M. Anasrul Dwi Novriansyah; Handayani Handayani; Amil Salim (Departement of Mathematics Education, 2024)
The purpose of this study is to describe the role of the school environment, factors that are inhibiting and supporting the formation of discipline and responsibility character of MTs Negeri 4 Musi Banyuasin students. This research uses a qualitative description method and is carried out at MTS Negeri 4 Musi Banyuasin. Data collection is carried out by observation, interviews and documentation. The results of this study show that the role of the physical environment of MTS Negeri 4 Musi Banyuasin is able to make students disciplined and more responsible because of the availability of facilities and student books. However, the availability of these student books cannot necessarily make students disciplined because they still need guidance. Meanwhile, the social environment is still not supportive for the formation of disciplined character. In contrast to the character of responsibility, the school social environment supports the formation of students' character of responsibility by guiding them to complete the tasks given by the teacher.